Hormonal contraception and the risk of HIV acquisition - Savadzadeh, Shahin; Hesami, Kajal (Advances in Nursing & Midwifery, 2016)
Abstract Introduction: More than 100 million women worldwide use hormonal contraceptive, including using DMPA or oral contraceptive. There is particular concern about a putative link between hormonal contraception and HIV infection. The aim of this review article was to evaluate the association between hormonal contraception use and risk of HIV infection Methods: We were retrieved through a systematic search of electronic databases such as PubMed, Science Direct, Elsevier, BMJ, JAMA by utilizing keywords HIV prevention, hormonal contraception, women’s` health, risk factors and human immunodeficiency virus (HIV). This search conducted for relevant literature published between 1989 and 2013. Finding: An estimated 40 million people live with human immunodeficiency virus (HIV) globally. Most HIV infected human are of reproductive age 15–49 years. Approximately 45% of women using hormonal contraceptions. Long term used of Progestin-only Injectable such as DMPA and NETEN, may cause thinning of cervico-vaginal mucosa, it may lead to abrasions that facilitate access of HIV to CD4+ target cells in submucosal tissue and increased simian immunodeficiency virus acquisition. Although the clinical significance of this thinning remains uncertain. Conclusions: The data do not support an association between use of oral contraceptives and increased risk of HIV acquisition. Nonetheless, family planning services are an important venue for HIV prevention activities Keywords: Hormonal Contraception, HIV, Risk Factors, Women Health